Service provision by agri-cooperatives engaged in high value markets - Donovan, J.; Stoian, D.; Foundjem, D.; Blare, T. (Global Forum for Rural Advisory Services, 2016)
Markets for agricultural products with special quality, environmental, and social attributes can provide a profitable outlet for poor farmers in developing countries. However, participation in high value markets requires that farmers commit to deliver pre-identified volumes on time and in the required form and quality – a tall order in many cases. Agri-cooperatives play an important role in linking farmers to these markets; they forge business relations with distant buyers, realise economies of scale in processing and marketing, and provide advisory and other services to help their members respond to buyer demands. Examples of these services include technical assistance, training, and input and credit provision. This note presents a practical approach by which cooperatives strengthen their ability to deliver impactful and financially sustainable services. In doing so, it recognises the challenges faced by cooperatives to design services that both meet the different needs of members and are financially sustainable. Too often cooperative services are supported by external actors with no clear vision of how to continue once project support terminates, leading to disrupted service offerings for members, and fragmented learning processes for cooperatives and their partners. Innovation is urgently needed in how services are designed, how they are implemented, and cost recovery mechanisms. At the heart of the approach lies a focus on joint learning among stakeholders – cooperatives, their business partners, government agencies, and non-government organisations (NGOs) – to better tackle the complexity inherent in the provision of effective services to poor farmers.